Inhibition of colorectal cancer cell growth by downregulation of M2-PK and reduction of aerobic glycolysis by clove active ingredients - Liu, Lin; Xing, Gang; Guo, Xiaoyi; Chen, Hui; Li, Jian; Wang, Jian; Li, Yaling; Liang, Gang; Liu, Minghua (Frontiers in Pharmacology, 2025)
Exploring the anti-tumor molecular mechanisms of traditional Chinese medicines has become an important strategy to develop novel anti-tumor drugs in the clinic. Several pharmacological studies have reported the antioxidant, antibacterial, anti-inflammatory, and anti-tumor effects of clove. Previously, we have shown that the active fraction from clove (AFC) can inhibit the growth of tumor cells, particularly colon cancer cells, in vitro. However, the mechanism of action regarding the anti-colon cancer activity of AFC, especially in aerobic glycolysis, has not been adequately investigated. In this study, we found that AFC significantly inhibited the growth of five types of colon cancer cells, downregulated the mRNA and protein levels of M2-type pyruvate kinase (PKM2), and reduced aerobic glycolysis capacity. Transfection of PKM2-siRNA mimicked the inhibitory effects of AFC on aerobic glycolysis in colon cancer cells. Furthermore, the highly expressed, tumor-specific targets c-myc and cyclin D1 in cells were also found to be downregulated following the action of AFC. In the HCT116 cell xenograft nude mice models, the results after AFC administration were consistent with those of the cellular experiments, while AFC caused less liver injury and weight loss than the conventional chemotherapeutic agent 5- fluorouracil (5-FU). In conclusion, AFC inhibits colon cancer growth by downregulating PKM2 to inhibit aerobic glycolysis and reduce the tumor-specific high expression of c-myc and cyclin D1. Future work should explore how it downregulates pyruvate kinase (PK) in the first place, along with the intrinsic mechanism between the downregulation of PKM2 and the downregulation of c-myc.